Characteristics and Driven Factors of Nitrous Oxide and Carbon Dioxide Emissions in Soil Irrigated with Treated Wastewater - Yan-dong XUE; Pei-ling YANG; Yuan-pei LUO; Yun-kai LI; Shu-mei REN; Yan-ping SU; Yong-tao NIU (Journal of Integrative Agriculture, 2012)
The reuse of treated wastewater in agricultural systems could partially help alleviate water resource shortages in developing countries. Treated wastewater differs from fresh water in that it has higher concentrations of salts, Escherichia coli and presence of dissolved organic matter, and inorganic N after secondary treatment, among others. Its application could thus cause environmental consequences such as soil salinization, ammonia volatilization, and greenhouse gas emissions. In an incubation experiment, we evaluated the characteristics and effects of water-filled pore space (WFPS) and N input on the emissions of nitrous oxide (N2O) and carbon dioxide (CO2) from silt loam soil receiving treated wastewater. Irrigation with treated wastewater (vs. distilled water) significantly increased cumulative N2O emission in soil (117.97 µg N kg−1). Cumulative N2O emissions showed an exponentially increase with the increasing WFPS in unamended soil, but the maximum occurred in the added urea soil incubated at 60% WFPS. N2O emissions caused by irrigation with treated wastewater combined with urea-N fertilization did not simply add linearly, but significant interaction (P<0.05) caused lower emissions than the production of N2O from the cumulative effects of treated wastewater and fertilizer N. Moreover, a significant impact on cumulative CO2 emission was measured in soil irrigated with treated wastewater. When treated wastewater was applied, there was significant interaction between WFPS and N input on N2O emission. Hence, our results indicated that irrigation with treated wastewater should cause great concern for increasing global warming potential due to enhanced emission of N2O and CO2.